Analisa Strategi Model Bisnis Pada Cheseroll Lezat - Madani, Wanda Nurul; Ali, Mochammad Mukti (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research analyzes Cheseroll Lezat's business model strategy using a SWOT analysis approach. Through this analysis, the author evaluates the internal and external factors influencing Cheseroll Lezat's business success. SWOT analysis consists of identifying strengths, weaknesses, opportunities, and threats, which provides a comprehensive overview of the current state of the business and the challenges faced in the market. Based on the SWOT analysis results, it is known that the strengths, weaknesses, threats, and opportunities of delicious chess-rolls are strongly influenced by internal strengths such as product quality and customer loyalty. In contrast, existing weaknesses, such as distribution limitations, can be overcome by taking advantage of growing market opportunities. This research also provides strategic recommendations to improve the competitiveness of the business in the future by capitalizing on existing opportunities and overcoming threats. SWOT strategy where delicious chess-rolls' strengths, weaknesses, threats, and opportunities are strongly influenced by internal strengths such as product quality and customer loyalty.